Case series of leech application in chronic Karappan - Anpuchelvi, S.; Sritharan, G. (Proceedings of the 4th Jaffna University International Research Conference, 2018)
Skin diseases are the most common health problem in worldwide and are associated with a considerable burden. Karappan (Eczema) is a skin ailment which cause psychological, social and financial burden on the patient and their families. Management of eczema with antibiotics, antihistamines, steroids ect, are available but even after their use relapse, recurrences and other complications are very common. The study was to assess the efficacy of leech application in the management of Karappan (Eczema) with standard clinical parameters. This study without control group was conducted with 27 patients having the classical symptoms of karappan (Eczema) and selected as per the inclusion and exclusion criteria. Minimum four sitting of leech application were carried out with 7 days interval and pre and post treatment evaluation of the patient was done with Eczema area and severity Index (EASI) SCORE, SCORE of atopic dermatitis (SCORAD) index and Dermatology Life Quality Index (DLQI). The total EASI score showed considerable reduction up to 54.45 % (p<0.01) and the SCORAD) index significantly reduced by 55% (p<0.01). The life quality of the patient calculated by DLQI and improved significantly by 62.36% (p<0.01). Leech application gives significant relief for the symptoms of Karappan (Eczema). The life quality of the patient also improved significantly after leech therapy. No adverse reaction was reported during the entire course of study.
Keywords: Karappan; Eczema; Dermatology; Leech application